Dynamics of physical trail construction and of trail usage in the leaf-cutting ant Atta laevigata - Bouchebti, Sofia; Travaglini, Raphael Vacchi [UNESP]; Forti, Luiz Carlos [UNESP]; Fourcassié, Vincent (Taylor & Francis, 2018)
Leaf cutting ants of the genus Atta build long lasting physical trails to exploit the vegetation around their nest. In this paper we investigated the dynamics of physical trail construction and usage in the leaf-cutting ant Atta laevigata. We assessed the average duration of physical trail construction in a pasture environment and estimated the impact of the change in the physiognomy of the terrain on ant speed, individual gross transport rate and rate of resource collection by taking into account the effects of confounding variables for each of these parameters. We also examined whether ants are able to adjust their foraging behaviour at the individual or collective level in order to maintain the same rate of vegetation return to their nest along the construction process. We found that a colony of A. laevigata needs between 4½ and 6½ days to complete a physical trail. The construction proceeded in a fairly uniform manner along the trail, suggesting that it is not the result of the coordinated action of a small group of specialized individuals progressing along the trail but rather of the sum of uncoordinated actions of individual workers. Ant speed increased by a 2.6 factor on a cleared trail compared to an uncleared trail and individual gross transport rate nearly doubled. However, there was no significant change along the construction process in traffic intensity, the proportion of ants returning to the nest with a piece of vegetation or the rate of resource delivery to the nest. The main benefit of trail construction is thus to mobilize less foragers on the trail to collect the same amount of food, leaving the possibility for the remaining workers to forage on other trails or to accomplish other tasks.
Keywords: construction; foraging; leaf-cutting ants; load transport; locomotory speed